Method for producing base polymer for adhesive

JP2025021678APending Publication Date: 2025-02-14MAXELL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023125569
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、粘着剤用ベースポリマーとして好適なポリマーが得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021678000001_ABST
    Figure 2025021678000001_ABST
Patent Text Reader

Abstract

To provide a method for producing a polymer which is suitable as a base polymer for an adhesive.SOLUTION: A method for producing a base polymer for an adhesive which is a polymer that contains a hydroxycarboxylic acid unit and a tri- or higher valent polyhydric alcohol unit and has a branch structure includes: a decomposition step (step S1) of heating and agitating a raw material containing a first polyester resin and a second polyester resin which is a polyester resin different from the first polyester resin to a melting point of a polyester resin having a lowest melting point of the polyester resins contained in the raw material or higher, in a reaction device, and obtaining a decomposition product; a drying step (step S2) of drying the decomposition product; and a polymerization step (step S3) of heating and agitating the decomposition product in a reduced pressure environment, after the drying step (step S2).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a base polymer for a pressure-sensitive adhesive, and more particularly to a method for producing a base polymer for a polyester-based pressure-sensitive adhesive. [Background technology]

[0002] It has been proposed to use a copolymer of a biodegradable polymer such as polylactic acid as an adhesive. For example, JP 2011-88959 A discloses an adhesive sheet using a polyester made of lactic acid and a dibasic acid. Non-Patent Document 1 proposes to use a copolymer of polylactic acid and polycaprolactone as an adhesive. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-88959 A [Non-patent literature]

[0004] [Non-Patent Document 1] Shinya Takahashi, "Proposal for adhesives using renewable resources including plant-derived ingredients," Convertec, Processing Technology Research Association, February 2009, pp. 103-108 [Non-Patent Document 2] Mengyuan Zhang et. al., “Synthesis of Poly(l-lactide-co-ε-caprolactone) Copolymer: Structure, Toughness, and Elasticity”, Polymers 2021, 13, 1270, https: / / doi.org / 10.3390 / polym13081270 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a method for producing a polymer suitable as a base polymer for pressure sensitive adhesives. [Means for solving the problem]

[0006] A method for producing a base polymer for adhesives according to one embodiment of the present invention is a method for producing a base polymer for adhesives, which is a polymer having a branched structure containing a hydroxycarboxylic acid unit and a polyhydric alcohol unit with a valence of three or more, and includes a decomposition step in which a raw material containing a first polyester resin and a second polyester resin, which is a polyester resin different from the first polyester resin, is heated and stirred in a reaction apparatus to a temperature equal to or higher than the melting point of the polyester resin with the lowest melting point among the polyester resins contained in the raw materials, to obtain a decomposition product, a drying step in which the decomposition product is dried, and after the drying step, a polymerizing step in which the decomposition product is heated and stirred in a reduced pressure environment, and in at least one of the decomposition step and the polymerizing step, a polyhydric alcohol with a valence of three or more is added to the raw material or the decomposition product, and in at least one of the decomposition step and the polymerizing step, a catalyst is added. Effect of the Invention

[0007] According to the present invention, a polymer suitable as a base polymer for pressure sensitive adhesives can be obtained. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a flow diagram of a method for producing a base polymer for a pressure-sensitive adhesive according to one embodiment of the present invention. [Figure 2A] FIG. 2A is a diagram for explaining an outline of the method for producing a base polymer for a pressure-sensitive adhesive according to the present embodiment. [Figure 2B] FIG. 2B is a diagram for explaining an outline of the method for producing a base polymer for a pressure-sensitive adhesive according to this embodiment. [Figure 2C] FIG. 2C is a diagram for explaining an outline of the method for producing a base polymer for a pressure-sensitive adhesive according to this embodiment. [Diagram 3]FIG. 3 is an example of the 1H-NMR spectrum of a base polymer for a pressure-sensitive adhesive. [Figure 4A] FIG. 4A is a diagram showing a part of the chemical structure of a base polymer for a pressure-sensitive adhesive. [Figure 4B] FIG. 4B is a diagram showing another part of the chemical structure of the base polymer for a pressure-sensitive adhesive. [Figure 4C] FIG. 4C is a diagram showing still another part of the chemical structure of the base polymer for a pressure-sensitive adhesive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present inventors have investigated methods for improving the performance of base polymers for polyester-based pressure-sensitive adhesives, and have obtained the following findings.

[0010] A polymer with a low glass transition temperature is preferable as a base polymer for adhesives. For example, the glass transition temperature of polylactic acid is about 60°C, and it is not suitable as a base polymer for adhesives by itself. In order to adjust the glass transition temperature, it is effective to use a copolymer of two or more polyester resins.

[0011] A polymer with low crystallinity is preferred as the base polymer for the adhesive. High crystallinity promotes solidification and reduces adhesiveness. In order to reduce crystallinity, it is preferable to use a random copolymer in which two or more polyester resins are irregularly bonded.

[0012] Polyester copolymers are generally produced by polymerizing two or more types of monomers. For example, a copolymer of polylactic acid and polycaprolactone is generally produced by ring-opening polymerization of L-lactide and ε-caprolactone. However, in this method, lactide, which is more reactive than caprolactone, polymerizes first, and caprolactone polymerizes later, resulting in a block polymer. Therefore, it is difficult to sufficiently reduce the crystallinity using this method.

[0013] The present inventors have found a method for producing a polyester copolymer that is completely different from the above-mentioned methods. Specifically, they have found that by heating and stirring two or more kinds of polyester resins (polyester resins as polymers, not monomers), decomposition and generation of ester bonds occur simultaneously, thereby obtaining a polyester copolymer. Furthermore, they have found that this method can reduce the crystallinity compared to conventional methods. The present invention has been completed based on these findings. Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.

[0014] [Method of manufacturing base polymer for adhesives] FIG. 1 is a flow diagram of a method for producing a base polymer for adhesives according to one embodiment of the present invention. This method is a method for producing a base polymer for adhesives, which is a polymer having a branched structure and includes a hydroxycarboxylic acid unit and a trihydric or higher polyhydric alcohol unit. This method includes a decomposition step (step S1) in which a raw material including a first polyester resin and a second polyester resin, which is a polyester resin different from the first polyester resin, is heated to a melting point of the polyester resin having the lowest melting point among the polyester resins included in the raw material and stirred in a reaction apparatus to obtain a decomposition product, a drying step (step S2) in which the decomposition product is dried, and a high molecular weight step (step S3) in which the decomposition product is heated and stirred in a reduced pressure environment after the drying step. This method also includes a trihydric or higher polyhydric alcohol being added to the raw material or the decomposition product in at least one of the decomposition step and the high molecular weight step, and a catalyst being added in at least one of the decomposition step and the high molecular weight step.

[0015] First, an outline of the manufacturing method according to the present embodiment will be described with reference to Figs. 2A to 2C. In this manufacturing method, a raw material 10 containing a first polyester resin 11 and a second polyester resin 12 is heated and stirred in a reaction apparatus (step S2, see Fig. 2A). As a result, decomposition and generation of ester bonds occur simultaneously, and a decomposition product 20, which is a low molecular weight polyester copolymer, is obtained (see Fig. 2B). After drying the decomposition product 20 (step S2), a polyhydric alcohol and a catalyst are added, and the mixture is heated and stirred under a reduced pressure environment to increase the molecular weight (step S3). As a result, a polymer 30 having a branched structure containing a hydroxycarboxylic acid unit and a polyhydric alcohol unit is obtained (see Fig. 2C).

[0016] The polyhydric alcohol and the catalyst may be added in the decomposition step (step S1). That is, in the production method according to the present embodiment, a trihydric or higher polyhydric alcohol may be added to the raw material or the decomposition product in at least one of the decomposition step (step S1) and the polymerizing step (step S3), and a catalyst may be added to the raw material or the decomposition product in at least one of the decomposition step (step S1) and the polymerizing step (step S3).

[0017] [Disassembly process] Each step is described in detail below. First, a raw material containing a first polyester resin and a second polyester resin, which is a polyester resin different from the first polyester resin, is heated to a temperature equal to or higher than the melting point of the polyester resin with the lowest melting point among the polyester resins contained in the raw material and stirred to obtain a decomposition product (decomposition step (step S1)).

[0018] The raw material may contain something other than the first polyester resin and the second polyester resin. For example, the raw material may further contain a polyester resin different from both the first polyester resin and the second polyester resin. Hereinafter, "the mass of the polyester resin contained in the raw material" means the sum of the masses of all the polyester resins contained in the raw material.

[0019] The polyester resin (including the first polyester resin and the second polyester resin) contained in the raw material is, but is not limited to, for example, polylactic acid, polycaprolactone, polybutylene succinate, polybutylene succinate adipate, polybutylene adipate terephthalate, etc. That is, the raw material may contain one or more selected from the group consisting of polylactic acid, polycaprolactone, polybutylene succinate, polybutylene succinate adipate, and polybutylene adipate terephthalate. The raw material preferably contains at least one of polylactic acid and polycaprolactone, and more preferably contains polylactic acid.

[0020] Each of the polyester resins contained in the raw materials preferably has a weight average molecular weight of 10,000 or more, and more preferably 20,000 or more.

[0021] When the raw material contains polylactic acid, the content of polylactic acid in the raw material is preferably 55% by mass or less. The lower limit of the content of polylactic acid is not particularly limited, but is, for example, 40% by mass, and preferably 45% by mass.

[0022] The polyester resin as the raw material is preferably pretreated into a powder or pellet form. Alternatively, a grinding device may be provided at the raw material inlet of the reactor so that the raw materials are ground simultaneously with the inlet. Two or more types of polyester resins may be fed one by one in order, or may be mixed in advance and fed at once.

[0023] As described above, at the stage of the decomposition step (step S1), one or both of a polyhydric alcohol (a trihydric or higher alcohol) and a catalyst (polymerization catalyst) may be added.

[0024] The polyhydric alcohol is a trihydric or higher alcohol. The trihydric or higher alcohol is, for example, one or more selected from the group consisting of trimethylolpropane, glycerin, erythritol, pentaerythritol, glucose, acrylic polyol, polyester polyol, polyether polyol, epoxy polyol, polyolefin polyol, fluorine-containing polyol, and polyvinyl alcohol, and among these, trimethylolpropane and pentaerythritol are preferred. The polyhydric alcohol is more preferably a tetrahydric or higher alcohol.

[0025] The amount of polyhydric alcohol (a polyhydric alcohol having a valence of three or more; the same applies hereinafter in this paragraph) added is preferably 0.10 to 0.50 parts by mass (phr) per 100 parts by mass of the polyester resin contained in the raw material. The lower limit of the amount of polyhydric alcohol added is preferably 0.20 parts by mass per 100 parts by mass of the polyester resin contained in the raw material. The upper limit of the amount of polyhydric alcohol added is preferably 0.40 parts by mass per 100 parts by mass of the polyester resin contained in the raw material.

[0026] The catalyst is, for example, one or more selected from the group consisting of Zn, Sn, Fe, Al, Ti, Zn oxide, Sn oxide, Fe oxide, Al oxide, Ti oxide, organometallic salts of Zn, organometallic salts of Sn, organometallic salts of Fe, organometallic salts of Al, and organometallic salts of Ti, and among these, Zn oxide and organometallic salts of Sn (e.g., Sn octylate) are particularly preferred.

[0027] The amount of catalyst added depends on the type of catalyst, but is preferably 0.01 to 10.0 parts by mass relative to 100 parts by mass of polyester resin contained in the raw material. The lower limit of the amount of catalyst added is preferably 0.1 parts by mass, more preferably 0.4 parts by mass, and even more preferably 0.8 parts by mass relative to 100 parts by mass of polyester resin contained in the raw material. The upper limit of the amount of catalyst added is preferably 5.0 parts by mass, and even more preferably 3.0 parts by mass relative to 100 parts by mass of polyester resin contained in the raw material.

[0028] The reactor may be any reactor capable of stirring the raw materials in a heated state. The reactor is preferably capable of controlling the atmosphere inside the reactor. Specifically, the reactor is preferably configured to be capable of sealing the inside except for the raw material inlet and outlet, gas inlet and outlet (vent), water inlet, and the like. The reactor is preferably made of metal, glass, or ceramic, and is particularly preferably made of metal. The reactor may be a batch type reactor or a continuous type reactor.

[0029] In the decomposition step (step S1), the moisture content at the time of decomposition, represented by the following formula, is preferably 0.015 or more (1.5% or more). Moisture content during decomposition = mass of moisture in the reactor / (mass of polyester resin contained in raw materials + mass of polyhydric alcohol + mass of catalyst) In the above formula, if no polyhydric alcohol is added, the "mass of polyhydric alcohol" is substituted with 0. Similarly, if no catalyst is added, the "mass of catalyst" is substituted with 0.

[0030] If the moisture content at decomposition is too low, the polyester resin may not be sufficiently decomposed, and it may be difficult to sufficiently reduce the crystallinity. The lower limit of the moisture content at decomposition is more preferably 0.100 (10.0%), further preferably 1.000 (100.0%), and further preferably 3.000 (300.0%). On the other hand, if the moisture content at decomposition is too high, the energy consumption for heating and drying increases. The upper limit of the moisture content at decomposition is preferably 10.000 (1000.0%), and more preferably 5.00 (500.0%).

[0031] The heating temperature during the decomposition step (step S1) (hereinafter referred to as "decomposition temperature") is a temperature equal to or higher than the melting point of the polyester resin having the lowest melting point among the polyester resins contained in the raw material. The higher the decomposition temperature, the easier the reaction proceeds. The lower limit of the decomposition temperature is preferably 150°C, more preferably 200°C, and even more preferably 230°C. The decomposition temperature may be equal to or higher than the melting point of the polyester resin having the highest melting point among the polyester resins contained in the raw material. On the other hand, if the decomposition temperature is too high, bonds other than ester bonds may be broken. The upper limit of the decomposition temperature is preferably 300°C, more preferably 280°C, and even more preferably 270°C.

[0032] The time for the decomposition step (step S1) (hereinafter referred to as "decomposition time") is not particularly limited, but is preferably 3 minutes or more. If the decomposition time is too short, the reaction does not proceed, and the crystallinity may not be sufficiently reduced. The lower limit of the decomposition time is more preferably 30 minutes, even more preferably 60 minutes, and even more preferably 90 minutes. The upper limit of the decomposition time is preferably 8 hours, even more preferably 6 hours, and even more preferably 3 hours.

[0033] The shear rate of stirring in the decomposition step (step S1) is preferably 50 to 1,000,000 / sec. If the shear rate is too low, the reaction may not proceed and the crystallinity may not be sufficiently reduced. On the other hand, if the shear rate is too high, bonds other than ester bonds may be broken. The lower limit of the shear rate is more preferably 100 / sec, further preferably 1,000 / sec, and further preferably 10,000 / sec. The upper limit of the shear rate is more preferably 500,000 / sec, and further preferably 300,000 / sec.

[0034] [Drying process] The decomposition product obtained in the decomposition step (step S1) is dried (drying step (step S2)).

[0035] The drying step (step S2) may be performed in the reaction vessel used in the decomposition step (step S1), or may be performed after transferring to a different vessel, etc. When the drying step (step S1) is performed using the reaction vessel used in the decomposition step (step S1), for example, the vent port of the reaction vessel may be operated in the high temperature state after the completion of the decomposition step (step S1) to discharge the moisture in the reaction vessel as steam, and the decomposition product may be dried by keeping it as it is for a predetermined time.

[0036] In the drying step (step S2), it is preferable to dry the material so that the moisture content after drying, expressed by the following formula, is 0.0015 or less (0.15% or less). Moisture content after drying = mass of moisture contained in decomposition product / (mass of polyester resin contained in raw material + mass of polyhydric alcohol + mass of catalyst) In the above formula, if no polyhydric alcohol is added, the "mass of polyhydric alcohol" is substituted with 0. Similarly, if no catalyst is added, the "mass of catalyst" is substituted with 0.

[0037] If the moisture content after drying is too high, the molecular weight may not be increased in the high molecular weight step. The upper limit of the moisture content after drying is more preferably 0.0013 (0.13%), and even more preferably 0.0012 (0.12%). The upper limit of the moisture content after drying is not particularly limited, but is preferably 0.0001 (0.01%), more preferably 0.0005 (0.05%), and even more preferably 0.0008 (0.08%) from the viewpoint of efficiency.

[0038] The heating temperature in the drying step (step S2) is preferably 80 to 140° C. If the heating temperature is too low, it is necessary to dry for a long time to reduce the moisture content. On the other hand, if the drying temperature is too high, the decomposition products will volatilize, resulting in a low yield.

[0039] The time for the drying step (step S2) is not particularly limited, but is preferably 30 to 160 minutes.

[0040] [High molecular weight process] After the drying step (step S2), the decomposition product is heated and stirred in a reduced pressure environment (polymerization step (step S3)).

[0041] The polymerizing step (step S3) may be carried out in the reaction vessel used in the decomposition step (step S1), or may be carried out after transferring to a different vessel or the like.

[0042] If a polyhydric alcohol and a catalyst are not added to the raw material in the decomposition step (step S1), a polyhydric alcohol and a catalyst are added to the decomposition product in the polymerizing step (step S3). As described above, in the manufacturing method of FIG. 3, a trihydric or higher polyhydric alcohol may be added to the raw material or the decomposition product in at least one of the decomposition step (step S1) and the polymerizing step (step S3), and a catalyst may be added to the raw material or the decomposition product in at least one of the decomposition step (step S1) and the polymerizing step (step S3). The preferred amount of addition, etc., is the same as when the catalyst is added in the decomposition step (step S1).

[0043] The heating temperature (hereinafter referred to as "polymerization temperature") in the high molecular weight step (step S3) is preferably 160 to 250°C. If the polymerization temperature is too high, the decomposition products may volatilize, resulting in a low yield. Furthermore, at even higher temperatures, the polymer may be thermally decomposed. On the other hand, if the polymerization temperature is too low, the molecular weight of the polymer may not be sufficiently large. The lower limit of the polymerization temperature is more preferably 180°C, even more preferably 200°C, even more preferably 210°C, and even more preferably 220°C. The upper limit of the polymerization temperature is more preferably 240°C.

[0044] The time of the high molecular weight step (step S3) (hereinafter referred to as "polymerization time") is preferably 30 to 480 minutes. If the polymerization time is too short, the molecular weight of the polymer may not be sufficiently large. On the other hand, if the polymerization time is too long, the polymer may gel (foam). If the polymerization time is too long, the molecular weight may become too high. If the molecular weight becomes too high, the glass transition temperature and storage modulus may become excessively high. The lower limit of the polymerization time is more preferably 60 minutes, and even more preferably 90 minutes. The upper limit of the polymerization time is more preferably 360 minutes, and even more preferably 300 minutes.

[0045] The shear rate of stirring in the polymerizing step (step S3) is preferably 50 to 1,000,000 / sec. If the shear rate is too low, the transesterification reaction may not proceed, and the crystallinity may not be sufficiently reduced. On the other hand, if the shear rate is too high, bonds other than the ester bonds may be broken. The lower limit of the shear rate is more preferably 100 / sec, further preferably 1,000 / sec, and further preferably 10,000 / sec. The upper limit of the shear rate is more preferably 500,000 / sec, and further preferably 300,000 / sec.

[0046] The degree of vacuum in the high molecular weight step (step S3) is preferably 1500 Pa or less, more preferably 1200 Pa or less, and further preferably 1000 Pa or less.

[0047] Through the above steps, a polymer having a branched structure containing hydroxycarboxylic acid units and trihydric or higher polyhydric alcohol units (base polymer for pressure sensitive adhesives) is produced.

[0048] [Base polymer for adhesives] The adhesive base polymer produced by the manufacturing method according to the present embodiment will be described below. The configuration of the adhesive base polymer described below is merely an example and does not limit the manufacturing method according to the present embodiment.

[0049] [structure] As described above, the pressure-sensitive adhesive base polymer is a polymer having a branched structure that contains hydroxycarboxylic acid units and trihydric or higher polyhydric alcohol units.

[0050] The hydroxycarboxylic acid unit is, but is not limited to, for example, a lactic acid unit or a caprolactone unit (a repeating unit of polycaprolactone).

[0051] The adhesive base polymer may contain structural units other than hydroxycarboxylic acid units and trihydric or higher polyhydric alcohol units. The adhesive base polymer may contain, for example, 1,4-butanediol units and succinic acid units (repeating units contained in polybutylene succinate), adipic acid units (repeating units contained in polybutylene succinate adipate), terephthalic acid units (repeating units contained in polybutylene adipate terephthalate), etc.

[0052] From the viewpoint of increasing the biomass degree, the adhesive base polymer preferably contains a lactic acid unit as a hydroxycarboxylic acid unit. When the adhesive base polymer contains a lactic acid unit, the proportion of the lactic acid unit in the polymer is preferably 20 to 50 mol%. If the proportion of the lactic acid unit is too high or too low, the preferable properties as an adhesive base polymer may not be obtained. The lower limit of the proportion of the lactic acid unit is more preferably 30 mol%, and even more preferably 40 mol%. The upper limit of the proportion of the lactic acid unit is more preferably 48 mol%, and even more preferably 46 mol%.

[0053] The polyhydric alcohol unit is a structural unit derived from the above-mentioned trihydric or higher alcohol. By making the polyhydric alcohol unit a structural unit derived from a trihydric or higher alcohol, the pressure-sensitive adhesive base polymer can have a branched structure, and the cohesive strength is improved.

[0054] The proportion of polyhydric alcohol units in the polymer is preferably 0.55 mol% or less. If the proportion of polyhydric alcohol units is too high, the polymer may gel (foam) and become unusable as a base polymer for adhesives. The upper limit of the proportion of polyhydric alcohol units is more preferably 0.50 mol%, and even more preferably 0.45 mol%. On the other hand, if the proportion of polyhydric alcohol units is too low, a branched structure may not be obtained sufficiently, and the glass transition temperature may not decrease. The lower limit of the proportion of polyhydric alcohol units is preferably 0.20 mol%, and even more preferably 0.30 mol%.

[0055] The base polymer for the PSA may be a polymer having a branched structure containing lactic acid units, caprolactone units, and trihydric or higher polyhydric alcohol units. Such a polymer can be produced, for example, by using polylactic acid as the first polyester resin and polycaprolactone as the second polyester resin.

[0056] When the base polymer for adhesives is a polymer containing lactic acid units and caprolactone units as described above, the proportion of the caprolactone units in the polymer is not particularly limited, but is, for example, 40 to 80 mol%. The lower limit of the proportion of the caprolactone units is preferably 50 mol%, more preferably 53 mol%. The upper limit of the proportion of the caprolactone units is preferably 70 mol%, more preferably 60 mol%.

[0057] Even when the adhesive base polymer is a polymer containing lactic acid units and caprolactone units as described above, the adhesive base polymer may further contain structural units other than lactic acid units, caprolactone units, and polyhydric alcohol units. The adhesive base polymer may, for example, contain hydroxycarboxylic acid units other than lactic acid units and caprolactone units. The proportion of structural units other than lactic acid units, caprolactone units, and polyhydric alcohol units in the polymer is preferably 10 mol % or less, more preferably 5 mol % or less, and even more preferably 1 mol % or less. The proportion of each unit in the polymer may be, for example, 1 It can be measured by H-NMR.

[0058] [Fα and Fε] When the adhesive base polymer is a polymer containing lactic acid units and caprolactone units as described above, it is preferable that at least one of Fα and Fε, represented by the following formula, is 0.35 or more. Fα=Iα * / (Iα+Iα * ) Fε=Iε * / (Iε+Iε * ) Here, Iα, Iα * , Iε and Iε * is a base polymer for adhesives. 1 A value obtained from a H-NMR spectrum, Iα is the integrated intensity of a signal derived from a proton of a methylene group that is bonded to a carbonyl carbon of an ester bond, among methylene groups contained in a caprolactone unit, and that is bonded to the caprolactone unit via the ester bond, Iα * is the integral intensity of a signal derived from a proton of a methylene group that is bonded to a carbonyl carbon of an ester bond, among methylene groups contained in a caprolactone unit, and that is bonded to a lactic acid unit via the ester bond, Iε is the integral intensity of a signal derived from a proton of a methylene group that is bonded to an oxygen atom of an ester bond among methylene groups contained in a caprolactone unit and is bonded to the caprolactone unit via the ester bond, Iε * is the integrated intensity of a signal derived from a proton of a methylene group that is bonded to an oxygen atom of an ester bond among methylene groups contained in a caprolactone unit and is bonded to a lactic acid unit via the ester bond.

[0059] FIG. 3 shows a pressure-sensitive adhesive base polymer containing lactic acid units and caprolactone units. 1 This is an example of a H-NMR spectrum. 1 The H-NMR spectrum was measured using a Bruker AVANCE NEO 700MHz nuclear magnetic resonance (NMR) spectrometer, with the adhesive base polymer dissolved in deuterated chloroform at 10 mg / ml. TMS (tetramethylsilane) was used as the chemical shift standard.

[0060] In FIG. 3, α, α * , β, γ, δ, ε and ε * are signals derived from the protons of the methylene groups contained in the caprolactone units. * are signals derived from the protons of the methyl groups contained in the lactic acid units, and B and B * is a signal derived from the proton of the methine group contained in the lactic acid unit.

[0061] 4A to 4C show a part of the chemical structure of a base polymer for adhesives containing lactic acid units and caprolactone units. This base polymer for adhesives contains lactic acid units LA (FIGS. 4B and 4C), caprolactone units CL (FIGS. 4A to 4C), and polyhydric alcohol units (not shown). As shown in FIG. 4A, the caprolactone unit CL has five methylene groups. These methylene groups are expressed as α-position, β-position, γ-position, δ-position, and ε-position methylene groups in the order of those directly bonded to the carbonyl carbon of the ester bond.

[0062] The methylene group at the α position is a methylene group bonded to the carbonyl carbon of the ester bond. The methylene group at the ε position is a methylene group bonded to the oxygen of the ester bond. The α to ε signals in Figure 3 are signals due to the protons of the methylene groups at the α to ε positions, respectively.

[0063] The signal derived from the proton of the methylene group at the α-position appears at a different chemical shift when the methylene group is bonded to the caprolactone unit CL via an ester bond (see FIG. 4A) and when it is bonded to the lactic acid unit LA via an ester bond (see FIG. 4B). Here, the methylene group bonded to the carbonyl carbon of the ester bond and bonded to the lactic acid unit LA via the ester bond is referred to as α. * The methylene group bonded to the caprolactone unit CL via the ester bond is represented as the methylene group at the α-position as described above (see FIG. 4A). * The signal of α * Specifically, the signal of α appears at about 2.30 to 2.35 ppm, while the signal of α * The signal appears at approximately 2.35 to 2.50 ppm.

[0064] Similarly, the signal derived from the proton of the methylene group at the ε position appears at a different chemical shift when the methylene group is bonded to the caprolactone unit CL via an ester bond (see FIG. 4A) and when it is bonded to the lactic acid unit LA via an ester bond (see FIG. 4C). Here, the methylene group bonded to the oxygen of the ester bond and bonded to the lactic acid unit LA via the ester bond is referred to as ε. * The methylene group bonded to the caprolactone unit CL via the ester bond is represented as the methylene group at the ε position as described above (see FIG. 4A). * The signal of ε *Specifically, the ε signal appears at about 4.00 to 4.10 ppm, whereas the ε signal appears at about 4.00 to 4.10 ppm. * The signal appears at approximately 4.10 to 4.20 ppm.

[0065] In addition, the signal derived from the proton of the methyl group of the lactic acid unit LA is also expressed as A or A depending on whether the partner of the ester bond is the lactic acid unit LA or the caprolactone unit CL. * It is observed as A * is a proton originally located at A that has been shifted downfield from A by binding to the caprolactone unit CL. Similarly, the signal originating from the methine group proton of the lactic acid unit LA is also shifted downfield from B or B. * It is observed as:

[0066] Iα, Iα * , Iε and Iε * are α, α * , ε and ε * is the integrated intensity of the signal. 1 The integrated intensity of the H-NMR signal is proportional to the number of protons. * , Iε and Iε * are α-position and α * ε position, ε position and ε * The amount is proportional to the number of protons in the methylene group at the

[0067] Therefore, Iα is a quantity proportional to the number of bonds between caprolactone units CL and CL (hereinafter referred to as "CL-CL bonds"), and Iα * is a quantity proportional to the number of bonds between caprolactone units CL and lactic acid units LA (hereinafter referred to as "CL-LA bonds"). Fα = Iα * / (Iα+Iα * ) is the ratio of the number of CL-LA bonds to the sum of the number of CL-CL bonds and the number of CL-LA bonds.

[0068] Similarly, Iε is a quantity proportional to the number of CL-CL bonds, and Iε *is a quantity proportional to the number of CL-LA bonds. Fε=Iε * / (Iε+Iε * ) is the ratio of the number of CL-LA bonds to the sum of the number of CL-CL bonds and the number of CL-LA bonds.

[0069] The larger Fα and Fε are, the higher the proportion of CL-LA bonds in the polymer. In other words, the larger Fα and Fε are, the more frequently caprolactone units CL and lactic acid units LA are switched, and the smaller the size of the block in which caprolactone units CL and lactic acid units LA are continuous.

[0070] The adhesive base polymer preferably has at least one of Fα and Fε of 0.35 or more (35% or more). If at least one of Fα and Fε is 0.35 or more, excellent adhesion can be obtained. The lower limit of Fα and Fε is more preferably 0.38 or more, and even more preferably 0.40 or more. At least one of Fα and Fε may be 0.35, 0.38 or 0.40 or more, and more preferably both Fα and Fε are 0.35, 0.38 or 0.40 or more. The upper limit of Fα and Fε is not particularly limited, but is, for example, 0.80, and preferably 0.60.

[0071] Although Fα and Fε have been described above when the adhesive base polymer is a polymer containing lactic acid units and caprolactone units, these descriptions are not intended to limit the adhesive base polymer produced by this embodiment to the above. The adhesive base polymer produced by this embodiment may be any polymer having a branched structure containing hydroxycarboxylic acid units and trivalent or higher polyhydric alcohol units.

[0072] [Glass transition temperature, etc.] The adhesive base polymer preferably has a glass transition temperature of -15°C or lower. If the glass transition temperature is too high, it is not suitable as an adhesive base polymer. The glass transition temperature can be adjusted by the molecular weight of the polymer, the ratio of lactic acid units and caprolactone units in the polymer, etc. The glass transition temperature is more preferably -20°C or lower, even more preferably -25°C or lower, and even more preferably -30°C or lower. The lower limit of the glass transition temperature is not particularly limited, but is, for example, -60°C.

[0073] The base polymer for pressure-sensitive adhesives preferably has a number average molecular weight Mn of 10,000 to 30,000 and a weight average molecular weight Mw of 40,000 to 100,000. The lower limit of the number average molecular weight Mn is more preferably 12,000, and even more preferably 13,000. The upper limit of the number average molecular weight Mn is more preferably 25,000, and even more preferably 20,000. The lower limit of the weight average molecular weight Mw is more preferably 45,000, and even more preferably 50,000. The upper limit of the weight average molecular weight Mw is more preferably 90,000, and even more preferably 80,000.

[0074] The dispersity (Mw / Mn) of the pressure-sensitive adhesive base polymer is, for example, 1.0 to 10.0. The lower limit of the dispersity is preferably 1.5, and more preferably 2.0. The upper limit of the dispersity is preferably 8.0, and more preferably 6.0.

[0075] The base polymer for the pressure-sensitive adhesive preferably has a storage modulus at 20° C. of 0.10×10 5 ~1.5×10 5 The lower limit of the storage modulus is more preferably 0.20×10 5 Pa, and more preferably 0.50×10 5 The upper limit of the storage modulus is more preferably 1.40×10 5 Pa, and more preferably 1.30×10 5 It is Pa. [Effects of this embodiment] The method for producing a base polymer for a pressure-sensitive adhesive according to one embodiment of the present invention has been described above. According to this embodiment, a polymer suitable as a base polymer for a pressure-sensitive adhesive can be obtained.

[0076] The adhesive base polymer produced by this embodiment can be used, for example, as an adhesive material constituting the adhesive layer of an adhesive tape. For example, the adhesive is prepared by adding a dilution solvent, a crosslinking agent (HDI, etc.), and other additives (tackifier, etc.) as necessary to the adhesive base polymer produced by the production method according to this embodiment. The adhesive tape is produced, for example, by applying an adhesive to a sheet-like substrate and drying it.

[0077] Products manufactured by the present invention can realize efficient use of resources and energy, utilization of renewable resources, and reduction of environmental burden. By providing the present invention to society, it is possible to contribute to the achievement of Goal 12 (Responsible Consumption and Production) of the 17 Sustainable Development Goals (SDGs) established by the United Nations. EXAMPLES

[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0079] Under the conditions shown in Tables 1 to 3, polyester resin was decomposed, dried, and polymerized to produce a polymer.

[0080] [Table 1]

[0081] [Table 2]

[0082] [Table 3]

[0083] In Tables 1 to 3, "PLA" represents polylactic acid with a number average molecular weight of 78,000 and a weight average molecular weight of 120,000, "PCL" represents polycaprolactone with a number average molecular weight of 15,000 and a weight average molecular weight of 25,000, "PBSA" represents polybutylene succinate adipate with a number average molecular weight of 40,000 and a weight average molecular weight of 123,000, and "PBAT" represents polybutylene adipate terephthalate with a number average molecular weight of 44,000 and a weight average molecular weight of 53,000. The melting point of polylactic acid was about 170°C, the melting point of polycaprolactone was about 60°C, the melting point of polybutylene succinate adipate was about 90°C, and the melting point of polybutylene adipate terephthalate was about 130°C.

[0084] In Tables 1 to 3, "A1" represents pentaerythritol, and "A2" represents trimethylolpropane. In Tables 1 to 3, "C1" represents tin octoate, and "C2" represents ZnO.

[0085] The various physical properties of the produced polymer were measured.

[0086] The proportion (mol%) of the polymer's structural units was measured by proton nuclear magnetic resonance ( 1 The compound was analyzed by H-NMR. 1 H-NMR spectra were measured using a JEOL ECA 500MHz nuclear magnetic resonance spectrometer, a Bruker AVANCE III HD 400MHz nuclear magnetic resonance spectrometer, and a Bruker AVANCE NEO 700MHz nuclear magnetic resonance spectrometer, with the adhesive base polymer dissolved in deuterated chloroform at 10mg / ml. TMS (tetramethylsilane) was used as the chemical shift standard.

[0087] The number average molecular weight Mn and the weight average molecular weight Mw were measured by dissolving the produced polymer in tetrahydrofuran at 0.5 wt % and subjecting it to gel permeation chromatography (GPC) using polystyrene as a standard substance.

[0088] The glass transition temperature Tg and heat of fusion were measured by differential scanning calorimetry (DSC). Using DSC, the temperature was first raised from -80°C to 200°C at a heating rate of 10°C / min to erase the thermal history, then the temperature was lowered to -80°C at a heating rate of 10°C / min, and again measured at a heating rate of 10°C / min. The heat of fusion was calculated from the area of ​​the endothermic peak that appeared in the DTA during the second heating. The glass transition temperature Tg was taken as the temperature indicating the inflection point of the transition region that appeared in the DTA during the second heating.

[0089] 1 The presence or absence of copolymer was confirmed from the 1 H-NMR spectrum, and Fα and Fε were determined.

[0090] The storage modulus at 20°C was measured as follows: Using an Anton Paar MCR301 viscoelasticity tester, a test sample with a thickness of 0.5 mm was measured with parallel plates with a diameter of 8 mm, and the storage modulus at 20°C was measured at a frequency of 1 Hz and a strain of 1%.

[0091] The results are shown in Tables 4 to 6.

[0092] [Table 4]

[0093] [Table 5]

[0094] [Table 6]

[0095] In Tables 4 to 6, LA represents a lactic acid unit, CL represents a caprolactone unit, BD represents a 1,4-butanediol unit, SA represents a succinic acid unit, AA represents an adipic acid unit, TP represents a terephthalic acid unit, A1 represents a polyhydric alcohol unit derived from pentaerythritol, and A2 represents a polyhydric alcohol unit derived from trimethylolpropane.

[0096] Incidentally, Fα and Fε in Production Examples 7 and 8 were determined as follows. Fα=Iα * / (Iα+Iα * ) Fε=Iε * / (Iε+Iε * ) Here, Iα, Iα * , Iε and Iε * is a base polymer for adhesives. 1 A value obtained from a H-NMR spectrum, Iα is the integrated intensity of a signal derived from a proton of a methylene group that is bonded to a carbonyl carbon of an ester bond, among methylene groups contained in a caprolactone unit, and that is bonded to the caprolactone unit via the ester bond, Iα * is the integral intensity of a signal derived from a proton of a methylene group, which is a methylene group contained in a caprolactone unit and is bonded to a carbonyl carbon of an ester bond and is bonded to a 1,4-butanediol unit via the ester bond, Iε is the integral intensity of a signal derived from a proton of a methylene group that is bonded to an oxygen atom of an ester bond among methylene groups contained in a caprolactone unit and is bonded to the caprolactone unit via the ester bond, Iε * is the total integrated intensity of signals derived from protons of methylene groups that are bonded to oxygen atoms of ester bonds among methylene groups contained in a caprolactone unit and that are bonded to any one of a succinic acid unit, an adipic acid unit, and a terephthalic acid unit via the ester bond.

[0097] As shown in Table 4, the polymers produced in Production Examples 1 to 6 had a glass transition temperature Tg of −15° C. or lower, and Fα and Fε of 35% or higher. These polymers had a storage modulus at 20° C. of 0.10×10 5 ~1.5×10 5The polymers produced in Production Examples 7 and 8 also had a glass transition temperature Tg of -15°C or lower and a storage modulus at 20°C of 0.10 × 10 5 ~1.5×10 5 The pressure was in the range of Pa.

[0098] The polymer of Production Example 11 had a large storage modulus and a high glass transition temperature. This is believed to be due to the fact that the proportion of polylactic acid in the raw material was too high.

[0099] The polymer of Production Example 12 had a small storage modulus, a high glass transition temperature, and small Fα and Fε. These are believed to be due to the absence of a polyhydric alcohol.

[0100] The polymer of Production Example 13 gelled (foamed) during the polymerization, which is believed to be due to the addition of too much polyhydric alcohol.

[0101] The polymer of Production Example 14 had a small storage modulus. This is believed to be because the molecular weight did not increase sufficiently due to the absence of a catalyst.

[0102] The polymer of Production Example 15 had a large storage modulus. In addition, the glass transition temperature was high and Fα and Fε were small. This is believed to be because the water content at the time of decomposition was too low.

[0103] The polymer of Production Example 16 had a large storage modulus. In addition, the glass transition temperature was high and Fα and Fε were small. This is believed to be because the decomposition temperature was too low.

[0104] The polymer of Production Example 17 had a large storage modulus. In addition, the glass transition temperature was high and Fα and Fε were small. This is believed to be because the decomposition time was too short.

[0105] The polymer of Production Example 18 had a large storage modulus and a high glass transition temperature. This is believed to be due to the shear rate of stirring during the decomposition process being too low.

[0106] The polymer of Production Example 19 had a small storage modulus. This is believed to be because the water content after drying was high, and therefore the molecular weight did not increase sufficiently.

[0107] The polymer of Production Example 20 had a small storage modulus. This is believed to be because the polymerization temperature was too low, and the molecular weight did not increase sufficiently.

[0108] The polymer of Production Example 21 did not have a sufficiently large molecular weight because the polymerization time was too short.

[0109] The polymer of Production Example 22 gelled (foamed) during polymerization, presumably because the polymerization time was too long.

[0110] The polymer of Production Example 23 had a high glass transition temperature. In addition, Fα and Fε were also small. This is believed to be due to the low shear rate of stirring during the polymerizing process.

[0111] The molecular weight of the polymer of Production Example 24 did not become sufficiently large because the degree of vacuum during the polymerizing step was insufficient.

[0112] The reference example in Table 6 is based on Figure 2B in Non-Patent Document 2 (Mengyuan Zhang et. al., “Synthesis of Poly(l-lactide-co-ε-caprolactone) Copolymer: Structure, Toughness, and Elasticity”, Polymers 2021, 13, 1270, https: / / doi.org / 10.3390 / polym13081270). 1 Fα and Fε were calculated from the “PLCL (1:1-18h)” data of the H-NMR spectrum.

[0113] In Non-Patent Document 2, these copolymers are produced by ring-opening polymerization of L-lactide and ε-caprolactone. "PLCL (1:1-18h)" is data on L-lactide and ε-caprolactone added in a blending ratio (molar ratio) of 1:1 and polymerization for 18 hours. Non-Patent Document 2 also describes data on polymerization times of 24 hours and 30 hours, but the values ​​of Fα and Fε were the largest for the data on polymerization times of 18 hours (Fα for the data for 24 hours was 25.2%, and Fα for the data for 36 hours was 23.9%). Non-Patent Document 2 also includes data on copolymers produced with blending ratios (molar ratios) of L-lactide and ε-caprolactone of 2:1 and 3:1, but the proportions of lactic acid units in these copolymers were even higher than those in the Reference Examples.

[0114] In the Reference Example, Fα and Fε were less than 35%, even though the proportion of lactic acid units was higher than in Production Examples 1 to 6. This shows that it is difficult to increase Fα and Fε in the conventional method of producing a copolymer by ring-opening polymerization of L-lactide and ε-caprolactone.

[0115] Although the embodiment of the present invention has been described above, the present invention is not limited to the above-mentioned embodiment, and various modifications are possible within the scope of the invention.

Claims

1. A method for producing a base polymer for a pressure-sensitive adhesive, which is a polymer having a branched structure and contains a hydroxycarboxylic acid unit and a trihydric or higher polyhydric alcohol unit, comprising the steps of: a decomposition step of heating and stirring a raw material containing a first polyester resin and a second polyester resin, which is a polyester resin different from the first polyester resin, in a reaction apparatus to a melting point equal to or higher than the melting point of the polyester resin having the lowest melting point among the polyester resins contained in the raw material, to obtain a decomposition product; A drying step of drying the decomposition product; A polymerizing step of heating and stirring the decomposition product in a reduced pressure environment after the drying step, In at least one of the decomposition step and the polymerizing step, a polyhydric alcohol having a valence of three or more is added to the raw material or the decomposition product, A method for producing a base polymer for pressure-sensitive adhesives, comprising adding a catalyst in at least one of the decomposition step and the polymerizing step.

2. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the raw material comprises one or more selected from the group consisting of polylactic acid, polycaprolactone, polybutylene succinate, polybutylene succinate adipate, and polybutylene adipate fullerate.

3. The method for producing a base polymer for a pressure-sensitive adhesive according to claim 1 , wherein the raw material contains at least one of polylactic acid and polycaprolactone.

4. The raw material includes polylactic acid, The method for producing a base polymer for pressure-sensitive adhesives according to claim 1 , wherein the proportion of polylactic acid in the raw material is 55% by mass or less.

5. the catalyst is one or more selected from the group consisting of Zn, Sn, Fe, Al, Ti, Zn oxide, Sn oxide, Fe oxide, Al oxide, Ti oxide, an organometallic salt of Zn, an organometallic salt of Sn, an organometallic salt of Fe, an organometallic salt of Al, and an organometallic salt of Ti; The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the amount of the catalyst added is 0.01 to 10.0 parts by mass per 100 parts by mass of the polyester resin contained in the raw material.

6. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the amount of the polyhydric alcohol added is 0.10 to 0.50 parts by mass per 100 parts by mass of the polyester resin contained in the raw material.

7. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1 , wherein in the decomposition step, the water content upon decomposition represented by the following formula is 0.015 or more. Moisture content during decomposition = mass of moisture in reactor / (mass of polyester resin contained in raw material + mass of polyhydric alcohol + mass of catalyst)

8. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1 , wherein the decomposition step lasts for 3 minutes or more.

9. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the shear rate of stirring in the decomposition step is 50 to 1,000,000 / sec.

10. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the heating temperature in the drying step is 80 to 140°C.

11. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the drying step lasts for 30 to 160 minutes.

12. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the shear rate of stirring in the polymerizing step is 50 to 1,000,000 / sec.

13. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1 , wherein in the drying step, the polymer is dried so that the moisture content after drying, represented by the following formula, is 0.0015 or less. Moisture content after drying = mass of moisture contained in decomposition product / (mass of polyester resin contained in raw material + mass of polyhydric alcohol + mass of catalyst)

14. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the heating temperature in the polymerizing step is 160 to 250°C.

15. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1, wherein the time for the polymerizing step is 30 to 480 minutes.

16. The method for producing a base polymer for pressure-sensitive adhesives according to claim 1 , wherein the degree of vacuum in the polymerizing step is 1500 Pa or less.

Citation Information

Patent Citations

  • Thermally peelable pressure-sensitive adhesive sheet

    JP2011088959A